Short-Term Temperature Response of Leaf Respiration in Different Subtropical Urban Tree Species - Xu, Man; Liáng, Lìyǐn L.; Kirschbaum, Miko U. F.; Fang, Shuyi; Yu, Yina (Frontiers in Plant Science, 2021)
Plant leaf respiration is one of the critical components of the carbon cycle in terrestrial ecosystems. To predict changes of carbon emissions from leaves to the atmosphere under a warming climate, it is, therefore, important to understand the thermodynamics of the temperature response of leaf respiration. In this study, we measured the short-term temperature response of leaf respiration from five different urban tree species in a subtropical region of southern China. We applied two models, including an empirical model (the Kavanau model) and a mechanistic model (Macromolecular Rate Theory, MMRT), to investigate the thermodynamic properties in different plant species. Both models are equivalent in fitting measurements of the temperature response of leaf respiration with no significant difference (p =0.67) in model efficiency, while MMRT provide an easy way to determine the thermodynamic properties, i.e. enthalpy, entropy and Gibbs free energy of activation, for plant respiration. We found a conserved temperature response in the five studied plant species, showing no difference in thermodynamic properties and the relative temperature sensitivity for different species at low temperatures (<42 ℃). However, divergent temperature response among species happened at high temperatures over 42 ℃, showing more than two-fold differences in relative respiration rate compared to that below 42 °C, although the causes of the divergent temperature response remain unclear. Notably, the convergent temperature response at low temperatures could provide useful information for land surface models to improve predictions of climate change effects on plant respiration.